Vaginal hysterectomy a safe option in non-descent uterus as compared to abdominal hysterectomy - Singh, Sona; Gajbhiye, Vishal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The objective of present study was to compare the advantage of vaginal hysterectomy over abdominal hysterectomy in non-descent uterus. Methods: A non-randomized controlled trial was carried out in the Bundelkhand Medical College, Sagar and associated hospital from October 2015 to September 2017. A total of 150 cases were included in the study. Out on 150, 75 underwent vaginal hysterectomy for non-descent uterus and other 75 underwent abdominal hysterectomy for similar indications. Results: Among total 150 cases, 75 were underwent non-descent vaginal hysterectomy and similar number of cases underwent abdominal hysterectomy. Common age group was 35-54 years. Commonest indication was DUB (48.7%). Postoperatively, complications were more common in those who underwent abdominal hysterectomy such as ambulation (18 hours), incidence of nausea, vomiting, abdominal discomfort, bladder injury and wound infection were less in vaginal hysterectomy compared to abdominal hysterectomy. It was also observed that blood transfusion requirement, operative timing and hospital stay (3 days) were less in vaginal hysterectomy group. Conclusions: Vaginal hysterectomy for benign gynecological disorders is a safe, effective, least invasive and is associated with lesser complications as compare to abdominal hysterectomy. Today in the era where patient is more cosmetically concern, vaginal hysterectomy for non-descent uterine disorder needs to be considered as good and safe option.